Examining the Salience of Marriage to Offending for Black and Hispanic Men. (15th April 2016) - Bersani, Bianca E.; DiPietro, Stephanie M.
Abstract : Despite a considerable body of research demonstrating the beneficial effects of marriage for criminal desistance, data limitations have resulted in much of this work being based on predominantly white, male samples. In light of the rapidly changing demographic landscape of the US—and particularly the tremendous growth in the Hispanic population—the question of whether the benefits of marriage are generalizable to racial and ethnic minorities is an important one. This research extends prior work on the relationship between marriage and offending by assessing whether the benefits of marriage for criminal offending extend to today's racial and ethnic minority populations. Using a contemporary sample of 3, 560 young adult Hispanic, black and white males followed annually for 13 years spanning the transition to adulthood, we find that while marriage is a potent predictor of desistance for all groups, the benefits of marriage vary substantially across both race and ethnicity.